Harnessing Social Media For Health Communication In Anambra State, Awka Metropolis - Maureen, Ejie Ifeoma; Ngantem, Linus Mun (Darul Yasin Al Sys, 2024)
The advancement in information and communication technologies coupled with the advent of the internet has changed the narrative in health communication just like every other endeavour globally. The adoption and usage of social media platforms in health communication and journalism generally has opened up many opportunities to be maximized. This study therefore is hinged on harnessing social media for health communication in Awka metropolis. Using Extended Parallel Processing Model as theoretical framework and in-depth interview as methodology among other things; the study examined the multifarious opportunities social media usage portends in health communication. Findings from the study indicated that social media usage in health communication in Nigeria has great prospects of increasing access to information as well as doctor patient relationship. In spite of that, misinformation and conspiracy theories constitute major challenges for social media usage in health communication. The study concluded that regulatory measures should be implemented in order to reduce the negative effects social media usage portends. The study also recommended that the government should also expedite actions in making and implementing regulatory measures to check on the misusage of social media that seems to be thriving at the moment.